Evaluating nasal cautery techniques in epistaxis. Issue 10 (7th October 2019) - Bastianpillai, J; Saxby, C; Coyle, P; Armstrong, A; Mohamid, W; Mochloulis, G
Abstract: Background: Silver nitrate cautery and bipolar electrocautery are commonly used in the treatment of epistaxis. Currently, there are no recommendations on optimum contact times or power for nasal cautery. ENT consultant practice in the UK has not previously been evaluated. Methods: This study examined the burn depth associated with silver nitrate (75 per cent concentration) cautery and bipolar electrocautery on porcine septum samples, using varying contact times and power. ENT consultants completed a survey evaluating their practice. Results and conclusion: ENT consultant practice of nasal cautery was shown to vary widely. Silver nitrate cautery with a contact time of less than 30 seconds does not cause a full thickness burn. The findings lend some support to bilateral cauterisation with silver nitrate. Bipolar electrocautery should be set at lower than 10 W and with a contact time of less than 4 seconds to reduce the risk of complications associated with a full thickness burn.